Service-Life Analysis and Effect of Grease Lubrication on Wear of ASB 6302-2RS Ball Bearing in the AST-MPV Machine - Rilo Chandra Muhamadin; Ilham Arifin Pahlawan; Alviani Hesthi Permata Ningtyas; Gilang Taufiqu Rachman; Baharudin Priwintoko; Fariz Wisda Nugraha; Yusuf Subagyo; Mohammad Rizqi Abdul Basyith (Akademi Inovasi Indonesia, 2026)
Bearings are critical elements for supporting shaft rotation in industrial equipment. In the AST-MPV detergent-packaging machine at PT. X, ASB 6302-2RS bearings frequently experience jamming because of detergent-dust contamination. This study analyzed bearing service life and evaluated, as an initial comparative observation, the effect of additional grease under detergent-water exposure. The analytical stage used rotational speed, load conversion, dynamic equivalent load, and nominal bearing-life calculation with standardized N and kN units. The experimental stage compared two specimens: bearing A with manually applied Black Grease NLGI 3 LA and bearing B without additional grease. Both specimens were immersed in a 2 kg detergent and 1 L water mixture for five days, rotated at 1000 rpm for 30 min and 1500 rpm for 30 min, and measured using caliper and dial indicator. The corrected spring deflection was 0.006 m, and the calculated service life was 3479.1223 h at 1930 rpm. Additional grease reduced radius wear from 0.52 mm to 0.13 mm and outer-diameter wear from 0.10 mm to 0.03 mm. These findings suggest that scheduled grease lubrication may reduce wear in detergent-contaminated environments, although replicated testing is required.